Dirāsah Tahlīliyah Liltadribāt Fī Kitāb Ta’lim Allughah Al’arabiah Lilshafi Al Awwal Almutawasiṯ Liwizārah Alsyu`ūn Aldīniyah Al Indūnisiyah ām 2020 - Ahmad Fahmi Hidayat; Arif Taufiqurrahman (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
This study aims to know the analysis of the exercises in the Arabic language teaching book for the first intermediate class of the Indonesian Religious Ministry in 2020, and this research is expected to help teachers to know the standards of good exercises, and as a reference source in knowing the training models in the Arabic language teaching book for the first intermediate class of the Religious Ministry indonesian 2020, It is expected that this research will help teachers to know the standards of good exercises, and as a reference source in knowing the training models in the Arabic language teaching book for the first intermediate class of the Indonesian Religious Ministry in 2020, in order to visualize the teacher in forming appropriate teaching strategies with the book’s training materials. This study relies on the analytical descriptive method, by looking at the exercises in the